Beyond Oaxaca-Blinder: Accounting for Differences in Household Income Distributions Across Countries - Bourguignon, Francois (World Bank, Washington, D.C., 2013)
The authors develop a microeconometric method to account for differences across distributions of household income. Going beyond the determination of earnings in labor markets, they also estimate statistical models for occupational choice and for conditional distributions of education, fertility, and nonlabor incomes. The authors import combinations of estimated parameters from these models to simulate counterfactual income distributions. This allows them to decompose differences between functionals of two income distributions (such as inequality or poverty measures) into shares because of differences in the structure of labor market returns (price effects), differences in the occupational structure, and differences in the underlying distribution of assets (endowment effects). The authors apply the method to the differences between the Brazilian income distribution and those of Mexico and the United States, and find that most of Brazil's excess income inequality is due to underlying inequalities in the distribution of two key endowments: access to education and to sources of nonlabor income, mainly pensions.